Guinea : Fourth Review under the Extended Credit Facility Arrangement, and Financing Assurances Review -Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2020)
Real growth is expected at 5.8 percent in 2020, supported by rebounding mining production and investment-led construction activity. Legislative elections and a referendum for a new constitution will be held in March and presidential elections by end-year. Protests against the referendum are ongoing. Risks of political and social instability are high. Covid-19. The baseline scenario is based on the initial global downward revisions to growth due to the COVID-19 outbreak and assumes no outbreak in Guinea. As of March 10, 2020, there was no declared coronavirus case in Guinea. As the situation evolves, the country authorities and staff are keeping a close watch on macroeconomic developments, needed policy responses, and their impact on financing needs.